SAT0575 Safety and efficacy of lutikizumab (ABT-981), an anti–interleukin-1 alpha/beta dual variable domain (DVD) immunoglobulin, in subjects with knee osteoarthritis: results from the randomised, double-blind, placebo-controlled, parallel-group phase 2 trial. (12th June 2018) - Fleischmann, R.; Bliddal, H.; Blanco, F.; Schnitzer, T.; Peterfy, C.; Chen, S.; Wang, L.; Conaghan, P.; Berenbaum, F.; Pelletier, J.-P.; Martel-Pelletier, J.; Vaeterlein, O.; et al.
Abstract : Background: Animal studies suggested that inhibiting IL-1α/β with lutikizumab (formerly, ABT-981) may reduce pain and slow structural progression in OA. Objectives: This study (NCT02087904 ; ILLUSTRATE-K) assessed the safety and efficacy of lutikizumab in subjects with knee OA. Methods: Subjects (n=350; 347 analysed) with Kellgren-Lawrence (KL) grade 2–3 knee OA, synovitis on MRI or US, and visual analogue scale knee pain score 4–8 (range, 0–10) were randomised to receive placebo (PBO) or lutikizumab 25, 100, or 200 mg subcutaneously (sc) every 2 wk (E2W) for 50 wk. The primary endpoints were change from baseline (BL) in WOMAC pain at wk 16 and change from BL in MRI synovitis at wk 26. Other endpoints included WOMAC function and OMERACT/OARSI response (wk 16, 26, and 52) MRI cartilage volume (wk 26 and 52), and x-ray joint space narrowing (JSN) (wk 52). Results: BL demographics and disease characteristics were balanced (KL grade 3, 36.0%%–38.8%; mean WOMAC pain (scale 0–50), 26.2–28.4). The primary endpoint of WOMAC pain at wk 16 improved significantly, compared with PBO, with lutikizumab 100 mg (p=0.050;), but not 25 mg (p=0.834) or 200 mg (p=0.415). WOMAC pain reduction in all lutikizumab groups was sustained from wk 16 to 52, but differences between lutikizumab and PBO for WOMAC pain and other key signs and symptoms were not significant (table 1). Synovitis-related imaging, cartilage volume endpoints, and JSN were similar between lutikizumab and PBO groups at wk 26 and 52. lutikizumab was well tolerated; serious adverse events (SAEs), treatment-related SAEs, and infections and serious infections were similar with lutikizumab vs PBO. Injection site reactions, grade 2/3 neutropenia, and discontinuations due to neutropenia were more frequent with lutikizumab vs PBO. Lutikizumab exposures reached steady state after wk 6 and were stable through wk 52. Pharmacodynamic responses (neutrophil and high-sensitivity CRP levels) plateaued at the 100 mg dose and data were similar at 200 mg. The low immunogenicity to lutikizumab did not meaningfully affect outcomes. Conclusions: Lutikizumab was generally well tolerated and met the primary endpoint of reduction in WOMAC pain at wk 16 compared with placebo at a dose of 100 mg, but not at 25 mg or 200 mg; cartilage thickness, synovitis, and other structural endpoints were similar between lutikizumab and PBO. Acknowledgements: AbbVie funded the study (NCT02087904 ), contributed to its design and participated in data collection, analysis and interpretation of the data, and in writing, review, and approval of the publication. Medical writing (funded by AbbVie): Richard M. Edwards, PhD, and Michael J. Theisen, PhD of CPS. Disclosure of Interest: R. Fleischmann Grant/research support from: AbbVie, Consultant for: AbbVie, H. Bliddal Consultant for: AbbVie Inc., Roche, Pfizer, Lilly, F. Blanco Consultant for: AbbVie Inc., Pfizer, UCB, Bristol, Roche, Bioiberica, Sanofi, Grünenthal, GlaxoSmithKline, Lilly, Janssen, Regeneron, TRB Chemedica (DISSCO), T. Schnitzer Grant/research support from: AbbVie, Consultant for: AbbVie, C. Peterfy Shareholder of: Spire Sciences, Inc. (which provides imaging services for clinical trials to multiple pharmaceutical companies), Employee of: Spire Sciences, Inc. (which provides imaging services for clinical trials to multiple pharmaceutical companies), S. Chen Shareholder of: AbbVie, Employee of: AbbVie, L. Wang Shareholder of: AbbVie, Employee of: AbbVie, P. Conaghan Consultant for: AbbVie Inc., Medivir, Merck Serono, Novartis, Pfizer, Speakers bureau: AbbVie, F. Berenbaum Consultant for: AbbVie, Pfizer, Regeneron, J.-P. Pelletier Consultant for: AbbVie, J. Martel-Pelletier Consultant for: AbbVie, O. Vaeterlein Employee of: Bioclinica, W. Liu Shareholder of: AbbVie, Employee of: AbbVie, G. Levy Shareholder of: AbbVie, Employee of: AbbVie, L. Zhang Shareholder of: AbbVie, Employee of: AbbVie, J. Medema Shareholder of: AbbVie, Employee of: AbbVie, M. Levesque Shareholder of: AbbVie, Employee of: AbbVie